When God rewrites your story : six keys to a transformed life from Namesake - LaGrone, Jessica (Abingdon Press, 2013)
Namesake is a six-week Bible study that explores the transformational power of God through the stories of biblical characters who met God and whose lives and names were changed forever. As you meet Abraham and Sarah, Jacob, Naomi, Daniel, Peter, and an unnamed woman, you will discover that God wants to be just as intimately involved in your story, offering you an identity that shines with the purpose for which you were created--to know God's Son, Jesus, and to become more and more like Him, bringing glory for His name's sake